Computational studies of the dynamics and spectroscopy of peptides - Hill, Rachel E. (2016)
Proteins play a crucial role in almost all biological processes. Developing a complete understanding of the link between their structure, dynamics and function is goal of many areas of scientific research. One tool with which the protein structure has been investigated is infrared (IR) spectroscopy. IR is a useful probe of protein structure because the amide I region (1600-1700 cm-1) is sensitive to the secondary structure elements such as alpha-helices and beta-sheets; different secondary structures give rise to different signatures in the IR spectrum. The drawback of traditional IR is that the amide I region is often broad and featureless and thus difficult to interpret. Two-dimensional infrared spectroscopy (2DIR) can improve on the structural sensitivity of IR by spreading the transitions over a second frequency domain resulting in off-diagonal peaks that quantify the coupling between molecular vibrations. The development of the technique has been greatly aided by computational calculations of 2DIR spectra, such as from molecular dynamics (MD) simulations. In this thesis we apply the exciton method to calculate IR and 2DIR of Leu-enkephalin, a pentapeptide that is involved in the mediation of pain in the body by binding to opioid receptors. The calculated IR show qualitative agreement with both previously calculated and experimental spectra. Previous calculations gave results only for a single structure in the gas phase, and we have expanded this work to including spectra from MD simulations. Our work contributes calculated spectra to aid further understanding of the dynamics of Leu-enkephalin, which may help in the search for more effective opioid analgesics. In addition to enkephalin, we investigated four variants of the enoyl-acyl carrier protein reductase enzyme InhA found in Mycobacterium Tuberculosis, the bacterium responsible for tuberculosis, which is a threat to global health. In particular, we investigate both wild type variants and mutant known to exhibit resistance to isoniazid, one of the front-line treatments for tuberculosis. Due to the size of the protein, it is currently not a suitable candidate for theoretical 2DIR calculations. Instead we used data extracted from the one exciton Hamiltonian to probe the structural dynamics of the different variants. Our work supports previous experimental results, in particular work that had suggested the importance of a ~20 residue binding loop in mediating isoniazid resistance, and suggest several residues as potential candidates for isotope-labelled 2DIR experiments. The work in this thesis provides a starting point for further investigation of the dynamics and calculated spectroscopy of both Leu-enkephalin and InhA.